Mise en responsabilité en période de transition en Guinée (2008) et Madagascar (2009) (African Journal of Law and Politics, 2023)
The great jubilations which characterized periods of political transitions in Guinea and Madagascar in 2008 and 2009 respectively with great hopes and expectations for change were quickly undermined by the rationality of the various actors involved. This rationality obscured the procedures for institutional accountability, which was the basis for the restoration of meaningful institutionalised political orders in the respective states. As a result, the goals of reforming the government administration could not be achieved within this time frame. These political actors rather focused on the pretext of mobilizing a multiplicity of reforms, which were tactically and politically aimed at eliminating those they considered as “enemies of the Republic”.